Homogeneous Noncompetitive Immunoassay Based on the Energy Transfer Between Fluorolabeled Antibody Variable Domains (Open Sandwich Fluoroimmunoassay). (October 1999) - Ueda, H.; Kubota, K.; Wang, Y.; Tsumoto, K.; Mahoney, W.; Kumagai, I.; Nagamune, T.
The antigen-dependent stabilization of an anti-hen egg lysozyme (HEL) antibody HyHEL-10 variable region was monitored with fluorescence resonance energy transfer (FRET) between fluorolabeled heavy chain (VH ) and light chain (VL ) fragments. The VH and VL fragments labeled with succinimide esters of fluorescein and rhodamine-X, respectively, were mixed in a cooled cuvette, and the change in fluorescence spectra upon antigen addition was monitored. When excited at 490 nm, significant decrease in the fluorescence at 520 nm and its increase at 605 nm were observed when an increasing amount of HEL was added to the mixture in the concentration range of 1–100 μg/mL. The assay, named open sandwich fluoroimmunoassay (FIA), is noncompetitive and homogeneous and can be conducted with one clone of antibody. With the use of appropriate antibodies, it is thought to be a quick and inexpensive alternative to the conventional laborious and/or expensive immunoassays.